Assessment of ICU nurses' competency towards delirium among critically ill patients - Mona Ibrahim Hebeshy; Samia Hussieny Gaballah; Noha Mohammed Ibrahim (BMC, 2024)
Abstract Background ICU nurses play a critical role in managing delirium in critically ill patients, yet their competency in this area remains under-explored. Aim To assess ICU nurses' competency including their knowledge, practice, and attitudes toward delirium among critically ill patients. Methods A correlational descriptive study was conducted with 67 nurses in the medical intensive care unit at Suez Canal University Hospitals. Data was collected using an online survey and analyzed using descriptive statistics, ANOVA, and Pearson's correlation. Results Nurses showed a moderate knowledge level (M = 8.55), a low practice level (M = 6.62), and positive attitudes (M = 21.65) toward ICU delirium. ANOVA results indicated significant differences in practice scores based on educational level, F (2, 64) = 3.361, p = .041, and in knowledge scores based on ICU experience, F(3, 63) = 6.455, p < .001. Nurses with Master of Science in Nursing (MSN) degrees had higher practice scores than those with diplomas or Bachelor of Science in Nursing (BSN) degrees. There were no significant differences in knowledge and attitude scores based on educational level or age. Gender differences were minimal, with male nurses slightly outperforming female nurses. Correlation analysis showed positive relationships between age, education, ICU experience, and ICU nurses' levels of knowledge and practice. Conclusion ICU nurses demonstrate a knowledge-practice gap in delirium management. Targeted educational interventions, mentorship programs, and a focus on practical skills are essential to enhance delirium care. Relevance to clinical practice These findings highlight the urgent need for comprehensive delirium education and training programs for ICU nurses. By improving nurses' knowledge and practice, healthcare organizations can significantly enhance the early detection, prevention, and management of delirium, ultimately leading to improved patient outcomes and reduced length of stay in the ICU.